Enhancing Mathematics Learning through Problem-Based and Digital Integration: A Study on Wordwall-Based Teaching Modules - Lisa Gustiana Bellatama; Hari Sumardi; Effie Muchlis; Hanifah Hanifah (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to determine the validity and practicality of a Problem-Based Learning (PBL) module integrated with the Wordwall application for teaching the topic of similarity in junior high school mathematics. Methodology: The research adopts the Plomp development model, which includes five systematic stages: preliminary investigation, design, realization/construction, test-evaluation-revision, and implementation. Data were collected using expert validation sheets and student practicality questionnaires to assess the quality and usability of the developed module. Main Findings: The results show that the PBL–Wordwall-integrated module achieved a validity score of 89.83% (Very Valid) and a practicality score of 88.5% (Very Practical). The high validity demonstrates that the module’s content, structure, and linguistic elements are consistent with curriculum standards and responsive to learners’ cognitive levels. Likewise, the high practicality indicates that teachers and students found the module engaging, interactive, and easy to apply in classroom settings. Novelty/Originality of this study: The novelty of this study lies in the integration of the PBL approach with digital gamification through Wordwall, creating an innovative learning environment that fosters problem-solving, critical thinking, and motivation simultaneously. Unlike traditional static modules, this design embeds real-world contextual problems within interactive digital activities, bridging pedagogical theory and technological application. This research contributes both theoretically and practically by offering a replicable model for blending inquiry-based learning with gamified platforms in mathematics education. Overall, the developed module is effective, feasible, and capable of enhancing students’ engagement, conceptual mastery, and collaborative learning in mathematics.